2017
DOI: 10.1037/rel0000106
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parental religiosity and emerging adult psychological adjustment: Moderated mediation by gender and personal religiosity.

Abstract: Religiosity has a great effect on how individuals view and live their lives, helping to determine their actions and thoughts. Several reviews have substantiated a positive relationship between religiosity and mental health. Parental religiosity also can be beneficial, as adolescents with religious parents tended to be less likely to engage in risky behaviors. Similarly, late adolescent religiosity has been shown to mediate the relationship between perceived parental religiosity and late adolescent psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 66 publications
4
29
1
Order By: Relevance
“…Specifically, the current study contributes to previous literature by examining both maternal and paternal variables, parental anxiety, and used participant gender as a moderating variable. Both perceived maternal and paternal religiosity predicted emerging adult religiosity likely due to the strong influence of parents on children, as found in other research (e.g., Pearce & Thornton, 2007; Stearns & McKinney, 2017a). Indeed, parents socialize the religiosity of their children by exposing them to religious beliefs and activities as well as by encouraging them to engage in religious communities (Boyatzis, 2006).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Specifically, the current study contributes to previous literature by examining both maternal and paternal variables, parental anxiety, and used participant gender as a moderating variable. Both perceived maternal and paternal religiosity predicted emerging adult religiosity likely due to the strong influence of parents on children, as found in other research (e.g., Pearce & Thornton, 2007; Stearns & McKinney, 2017a). Indeed, parents socialize the religiosity of their children by exposing them to religious beliefs and activities as well as by encouraging them to engage in religious communities (Boyatzis, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…The current study found that the father–daughter bond may facilitate the transmission of religiosity (Halgunseth et al, 2016; Stearns & McKinney, 2017a, 2017b). This association may be related to females being more religious in general, thus boosting the transmission of religiosity within the father–daughter dyad (Boyatzis, 2006).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations